Evolution of the global temperature structure of the solar corona during the minimum between solar cycles 23 and 24 - Manchester IV, W.B. (2013)
The combination of differential emission measure tomography with extrapolation of the photospheric magnetic field allows determination of the electron density and electron temperature along individual magnetic field lines. This is especially useful in quiet-Sun (QS) plasmas where individual loops cannot otherwise be identified. In Paper I, this approach was applied to study QS plasmas during Carrington rotation (CR) 2077 at the minimum between solar cycles (SCs) 23 and 24. In that work, two types of QS coronal loops were identified: "up" loops in which the temperature increases with height, and "down" loops in which the temperature decreases with height. While the first ones were expected, the latter ones were a surprise and, furthermore, were found to be ubiquitous in the low-latitude corona. In the present work, we extend the analysis to 11 CRs around the last solar minimum. We found that the "down" population, always located at low latitudes, was maximum at the time when the sunspot number was minimum, and the number of down loops systematically increased during the declining phase of SC-23 and diminished during the rising phase of SC-24. "Down" loops are found to have systematically larger values of β than do "up" loops. These discoveries are interpreted in terms of excitation of Alfvén waves in the photosphere, and mode conversion and damping in the low corona. © 2013. The American Astronomical Society. All rights reserved..